The effect of void defect on the evolution mechanisms of dislocations and mechanical properties in nickel-based superalloys by molecular dynamics simulation of real γ/γ′ structures. (15th May 2020) - Liu, H.; Wang, X.M.; Liang, H.; Zhao, Z.N.; Li, L.; Yue, Z.F.; Deng, C.H.
Abstract: It is acknowledged that voids are unavoidable manufacture defects influencing the microstructure evolution and mechanical properties of nickel-based superalloys. The present work investigates the influences of void on the dislocation evolution and mechanical properties of nickel-based superalloys under different thermal conditions and strain rates. The simulation uses an embedded cubic model with voids in which the γ′ phase with L12 structure is surrounded by γ phase with FCC structure to represent the real microstructure of single crystal superalloys. A model without voids is also studied. The existence of voids changes the misfit dislocation network by introducing cylindrical dislocation network around the voids which play a vital role on preventing the void coalescence at low strain. Dislocation extraction algorithm (DXA) analysis finds that new type of dislocation appears in the model with voids and the dislocation length is longer. The elastic modulus and yield strength are decreased by voids, as well as the ductility of the material. This paper demonstrates that the accumulation and reaction between dislocations are the most direct reason for declining the mechanical properties of nickel-based superalloys with void defects.